Transition to light sail acceleration using ultraintense femtosecond pulses - Martin,P; Doria,D; Romagnani,L; Ahmed,H; McIlvenny,A; Scullion,C; Williamson,SDR; Ditter,EJ; Hicks,G; Ettlinger,OC; Scott,GG; Symes,DR; et al. (2017)
Presented are results from experimental campaigns undertaken on the Gemini laser system at the Central Laser Facility in the UK. In these experiments amorphous carbon targets ranging in thickness from 10nm to 100nm were irradiated with high contrast 40fs pulses with an intensity up to 1021 W/cm2, for both circular and linear polarisations and the resulting proton and ion spectra compared. Examining the highest energies achieved for a given polarisation and target thickness, allows to identify the transition from TNSA to LS. Observations of the optimal target thickness for ion acceleration are compared to analytical predictions from LS theory, in addition to results from Particle in Cell modelling.